Mixing of High Ductile Mortar (HDM) in Concrete Mixers - Gyawali, Tek Raj (Journal of Engineering Technology and Planning, 2019)
Plain concrete is strong in compression, but very weak in tension. Tensile strength of plain concrete is about10 to 15% of the compressive strength depending upon the grade of concrete. Another limitation of plain concrete is that it is brittle in failure. Fiber-reinforced concrete (FRC) is the concrete made primarily of hydraulic cements, aggregates, and discrete reinforcing fibers. Fibers suitable for reinforcing concrete are produced from steel, glass, and organic polymers (synthetic fibers). Author hereby has attempted to develop the High Ductile Mortar (HDM) using Poly Vinyl Alcohol (PVA) fibers. HDM may replace the steel fibers to increase the flexural strength and deflection. It also lightens the structure than steel fiber reinforced concrete (SFRC). This paper gives the brief history of HDM development results which were mixed in small mortar mixer of 10 liter capacity. Then, it presents the results of HDM mixed in two different concrete mixers of 100 liter capacity using different PVA fibers and sands.